Uncovering zoonoses awareness in an emerging disease ‘hotspot’ - Paige, Sarah B.; Malave, Carly; Mbabazi, Edith; Mayer, Jonathan; Goldberg, Tony L. (Social Science & Medicine, 2015)
Emerging infectious diseases from animals pose significant and increasing threats to human health; places of risk are simultaneously viewed as conservation and emerging disease ‘hotspots’. The One World/One Health paradigm is an ‘assemblage’ discipline. Extensive research from the natural and social sciences, as well as public health have contributed to designing surveillance and response policy within the One World/One Health framework. However, little research has been undertaken that considers the lives of those who experience risk in hotspots on a daily basis. As a result, policymakers and practitioners are unable to fully comprehend the social and ecological processes that catalyze cross-species pathogen exchange. This study examined local populations' comprehension of zoonotic disease. From October 2008–May 2009 we collected data from people living on the periphery of Kibale National Park, in western Uganda. We administered a survey to 72 individuals and conducted semi-structured, in-depth interviews with 14 individuals. Results from the survey showed respondents had statistically significant awareness that transmission of diseases from animals was possible compared to those who did not think such transmission was possible (x2 = 30.68, df = 1, p < 0.05). However, individual characteristics such as gender, occupation, location, and age were not significantly predictive of awareness. Both quantitative and qualitative data show local people are aware of zoonoses and provided biomedically accurate examples of possible infections and corresponding animal sources (e.g., worm infection from pigs and Ebola from primates). Qualitative data also revealed expectations about the role of the State in managing the prevention of zoonoses from wildlife. As a result of this research, we recommend meaningful discourse with people living at the frontlines of animal contact in emerging disease and conservation hotspots in order to develop informed and relevant zoonoses prevention practices that take into account local knowledge and perceptions.